Pengaruh Penerapan Model Problem Based Learning terhadap Keterampilan Berpikir Ilmiah dan Hasil Belajar Siswa - Rahayu Maharani, Devia; Muna, Khairiatul (Tadris Biologi, Tadris Fisika, and Tadris Kimia, Universitas Islam Negeri Antasari, 2024)
In the era of society 5.0, scientific thinking skills are very important to help students solve problems effectively. However, in practice, learning is still centered on the teacher, making students less active and tend to be passive in the learning process. This study aims to determine the effect of the Problem Based Learning (PBL) learning model on scientific thinking skills and student learning outcomes on the reaction rate material at MAN 3 Banjar. The method used is quasi-experimental with posttest only control group design with ANOVA Two Ways statistical test. The respondents of this study were 45 students of class XI MIA MAN 3 Banjar with a saturated sampling technique. The study was divided into two groups, namely the experimental class and the control class. The results of the study found that (1) the PBL learning model has a significant effect on scientific thinking skills with an F value of 2,664 or sig. <0.034. (2) the PBL learning model has a significant effect on learning outcomes with an F value of 30.054 or sig. <0.000. This study provides recommendations for learning models that are more effective and useful for scientific thinking skills and student learning outcomes.